2019
DOI: 10.1007/s11136-019-02297-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life measures in older adults after traumatic brain injury: a systematic review

Abstract: BackgroundOn average older adults experiencing TBI are hospitalized four times as often, have longer hospital stays, and experience slower recovery trajectories and worse functional outcomes compared to younger populations with the same injury severity. A standard measure of Qol for older adults with TBI would facilitate accurate and reliable data across the individual patient care continuum and across clinical care settings, as well as support more rigorous research studies of metadata.PurposeThe aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…An analysis of quality of life showed that older persons had regular assessment with percentage of the WHOQOL-OLD (54.8%) and the WHOQOL-BREF (57.4%), with the lowest assessments occurring for physical, social, environment, autonomy, past, present and future and social participation. The results of this study are similar when compared to studies that analyzed older persons in different socio-contextual and health situations, which leads us to rethink health and policy actions related to health promotion of older persons related to active aging (19,(26)(27)(28) .…”
Section: Discussionsupporting
confidence: 71%
“…An analysis of quality of life showed that older persons had regular assessment with percentage of the WHOQOL-OLD (54.8%) and the WHOQOL-BREF (57.4%), with the lowest assessments occurring for physical, social, environment, autonomy, past, present and future and social participation. The results of this study are similar when compared to studies that analyzed older persons in different socio-contextual and health situations, which leads us to rethink health and policy actions related to health promotion of older persons related to active aging (19,(26)(27)(28) .…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies assessing the impact of TBI on QoL in older adults have primarily focused on symptom reduction and input from family on clinical status. 10 However, there is now a growing recognition of the importance of considering the patient's perspective on QoL after TBI. To gain a better understanding of older adults' unique needs, advance clinical practice, enhance health care delivery, inform health policy, and allocate health services funds effectively, it is crucial to establish a standardized measurement for assessing QoL in older adults post-TBI.…”
Section: Qol Assessmentmentioning
confidence: 99%
“…9 The financial impact of TBI on patients, caregivers, and the health care system is substantial, with annual hospital charges exceeding 8.2 billion for the treatment of TBI in older adults. 10 This review aims to highlight the specific considerations and challenges faced by older adults with TBI.…”
mentioning
confidence: 99%
“…Research on both health-related quality of life (HRQoL) and psychological outcomes in older adults after TBI is scarce. Previous HRQoL studies included small sample sizes and few studies included both generic and disease-specific measures of HRQoL [19] . In some studies, individuals showed a higher risk for emergence of psychiatric disorders including depression, anxiety and posttraumatic stress disorder (PTSD) after TBI [20] , whereas in other studies older adults reported less psychological distress and less symptoms of depression and anxiety than younger adults [14] .…”
Section: Introductionmentioning
confidence: 99%